CREATING NARRATIVES AND REVISION CIRCLE: LITERACY DIMENSION LEARNING STRATEGIES USING DIDACTIC VALUES OF M.KASIMâ€™S FUNNY SHORT STORIES - Halimah, Halimah; Sumiyadi, Sumiyadi; Damaianti, Vismaia (Jurnal Pendidikan Bahasa dan Sastra, 2018)
Creating narratives and revision circle are the collaboration of two learning strategies of literacy dimensions. In literacy learning, students can develop a narration as a skill in literacy, particularly basic literacy in form of reading and writing. The present research aims at describing 2 strategies of literacy dimension learning through the analysis of didactic values from funny short stories written by M. Kasim. The funny short stories provided a variety of specific didactic values. As one of the literature learning materials, the didactic values were in line with the national education goals. The present research employed qualitative approach with a descriptive method. Specifically, the data were analyzed by the application of literary work didactic study framework. The funny short stories to analyze entitled: 1) â€œPendikar bukan Pendekar; 2) â€œPodato yang Gagalâ€; 3) â€œAda Seorang Rajaâ€¦â€, and Â 4) â€œKue yang Nakalâ€.Â  The result denoted the funny short stories contained various didactic values which could be regarded as learning materials in literacy development. The didactic values consisted of well-mannered behavior, dignified personality, independence, creativity, being democratic, responsibility, self-control, intelligence, and skill. Those values are considered excellent to implement by the collaboration of creating narratives and revision circle.